Raynaud’s Phenomenon in A Patient with Scleroderma: A Case Report - Patricia Hutagalung; Kristo Alberto Nababan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Systemic sclerosis, or scleroderma, is a chronic autoimmune disorder characterized by fibrosis of the skin and internal organs, vasculopathy, and immune dysregulation. Raynaud’s phenomenon (RP), marked by episodic vasospasm of the digital arteries in response to cold exposure or emotional stress, is often one of the earliest and most common sign of SSc. Early diagnosis plays a crucial role in preventing and managing complications of RP, such as digital ulcers and tissue damage due to chronic circulatory impairment, as well as in reducing long-term disability. This case report aims to highlight pedal ulcers as a complication of RP scleroderma and to emphasize the importance of early intervention in preventing progressive tissue damage. The data was conducted through a comprehensive approach including history assessment, physical examinations, electronic medical record reviews, laboratory diagnostics, and imaging studies to ensure accurate diagnosis and effective interventions. We report a 26-year-old woman who presented with a six-month history of progressive skin thickening and hardening involving almost all of her body. The patient also experienced finger stiffness, flexion contractures, and limited mouth opening. Dermatological examination revealed sclerotic skin with hypopigmented and hyperpigmented patches forming a